Advancing Building Energy Management System to Enable Smart Grid Interoperation - Eun-Kyu Lee (International Journal of Distributed Sensor Networks)
With the emerging concept of smart grid, a customer's building facility is able to consume, generate, and store energy. At the center of the facility, an energy management system is required to perform an efficient energy management and to enable smart grid interoperation. However, the existing EMS is designed only for the management function and does not support the interoperation. To resolve the issue, this paper designs the interoperation function and proposes a new EMS model, named Premises Automation System (PAS), that also inherits the existing management function. To identify functional requirements, we bring out four design aspects out of energy services. Then, we design two categories of interoperable energy services to achieve customer interoperation. To demonstrate the feasibility of PAS, we implement and deploy a testbed in a campus. We conduct experiments with a microgrid scenario and present interesting measurements and findings.